LncRNA GClnc1 promotes proliferation and invasion of bladder cancer through activation of MYC. Issue 10 (12th July 2019) - Zhuang, Chengle; Ma, Qian; Zhuang, Changshui; Ye, Jing; Zhang, Fangting; Gui, Yaoting
ABSTRACT: Various studies demonstrate that long noncoding RNAs (IncRNAs) act as oncogenes or tumor suppressors in cancer. However, the function of IncRNAs in bladder cancer still remains largely unknown. In this study, we identified an IncRNA, gastric cancer–associated IncRNA1 (GClnc1), which was in high abundance in bladder cancer tissues and its expression was related to poor survival rates in patients with bladder cancer. In vitro and in vivo assays showed that GClnc1 significantly promoted cell proliferation, metastasis, and invasiveness in bladder cancer. Mechanistically, we first found that GClnc1 bound to LIN28B and promoted the expression of myelocytomatosis proto‐oncogene (MYC) through the LIN28B/let‐7a/MYC pathway. In short, GClnc1 is clinically, functionally, and mechanistically oncogenic in bladder cancer. GClnc1 may be a potential target for treating patients with bladder cancer.—Zhuang, C., Ma, Q., Zhuang, C., Ye, J., Zhang, F., Gui, Y. LncRNA GClnc1 promotes proliferation and invasion of bladder cancer through activation of MYC. FASEB J. 33, 11045–11059 (2019). www.fasebj.org